Towards conservation and sustainable use of an indigenous crop: A large partnership network enabled the genetic diversity assessment of 1539 fonio (Digitaria exilis) accessions - Thomas Kaczmarek; Sandrine Causse; Suleiman D. Abdul; Solomon Abraham; Enoch G. Achigan‐Dako; Charlotte Adje; Joseph Adjebeng‐Danquah; Richard Y. Agyare; Louise Akanvou; Yacoubou Bakasso; Mamadou B. Barry; Samuel K. Bonsu; et al. (Plants, People, Planet)
Social Impact Statement The use of neglected and underutilized species (NUS) in agrosystems is a potential solution to the challenges arising from global change. These species could contribute to the equitable diversification of agricultural systems. Providing knowledge on their genetic diversity and fostering access to data and results is essential for the development of strong collaborative future research. The study addressed these issues by assessing the diversity of the largest fonio (Digitaria exilis) collection existing to date. Associated with a user‐friendly Shiny application (https://shinyapps.southgreen.fr/app/foniodiv), our results reinforce research efficiency and broaden the prospects for all actors involved in enhancing fonio and indigenous crops as valuable resources for the future.